Extreme sensitivity of dye solar cells to UV-induced degradation - Aapo Poskela; Kati Miettunen; Armi Tiihonen; Peter D. Lund (WILEY, 2022)
Present practice to avoid harmful effects of UV light on dye solar cells (DSC) is to use a UV filter. However, we show here that a standard 400 nm UV cutoff filter offers inadequate protection from UV-induced degradation. DSCs that were exposed to only visible light by LED lamps maintained 100% of their initial efficiency after 3000 hours of exposure, whereas the efficiency of DSCs subjected to full light spectrum (Xenon arc lamp) with an efficient UV filter dropped down to 10% of their initial performance already after 1500 hours. Optical analysis of the UV filter confirmed that the amount of light transmitted below 400 nm was negligible. These observations indicate that (a) DSCs can be very sensitive to even minor amount of UV and (b) eliminating the effects of UV light on DSC stability cannot easily be avoided by a UV filter on top of the cell. A detailed analysis of the degradation mechanisms revealed that the culprit to loss of performance was accelerated loss of charge carriers in the electrolyte of the DSCs-a typical symptom of UV exposure. These results suggest that commonly used stability tests under LED illumination are insufficient in predicting the lifetime of DSCs in outdoor conditions. Instead, for such purpose, we recommend solar cell stability to be tested with a full light spectrum and with a suitable UV filter.